Impact of Nicotine Transport across the Blood–Brain Barrier: Carrier-Mediated Transport of Nicotine and Interaction with Central Nervous System Drugs - Hosoya, Ken-ichi; Yamazaki, Yuhei; Akanuma, Shin-ichi; Tega, Yuma; Kubo, Yoshiyuki (Biological & pharmaceutical bulletin, 2018)
Nicotine, an addictive substance, is absorbed from the lungs following inhalation of tobacco smoke, and distributed to various tissues such as liver, brain, and retina. Recent in vivo and in vitro studies suggest the involvement of a carrier-mediated transport process in nicotine transport in the lung, liver, and inner blood–retinal barrier. In addition, in vivo studies of influx and efflux transport of nicotine across the blood–brain barrier (BBB) revealed that blood-to-brain influx transport of nicotine is more dominant than brain-to-blood efflux transport of nicotine. Uptake studies in TR-BBB13 cells, which are an in vitro model cell line of the BBB, suggest the involvement of H+/organic cation antiporter, which is distinct from typical organic cation transporters, in nicotine transport at the BBB. Moreover, inhibition studies in TR-BBB13 cells showed that nicotine uptake was significantly reduced by central nervous system (CNS) drugs, such as antidepressants, anti-Alzheimer’s disease drugs, and anti-Parkinson’s disease drugs, suggesting that the nicotine transport system can recognize these molecules. The cumulative evidence would be helpful to improve our understanding of smoking-CNS drug interaction for providing appropriate medication.